RAGAM METODE PENDIDIKAN KARAKTER DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) - Abdul Aziz Saefudin (Jurnal Pendidikan Agama Islam, 2012)
This article aims to discuss some very important methods to implement character education in PAI learning. Some of the methods mentioned, among others, tadzkiroh method, cjishah method, method, hiwar method amtsal. method, a method of conditioning uswah, ibrah and mau’dah methods, and tarhib method. The various methods of character education if implemented in PAI learning is expected to be the means of instilling positive characters to students. As a result, students are not only clever intellectually, emotionally and spiritually, but also have a strong character so internalized in daily life until later adulthood.